2009
DOI: 10.1007/s11258-009-9612-5
|View full text |Cite
|
Sign up to set email alerts
|

Allometry and effects of extreme elevation on growth velocity of the Andean tree Polylepis tarapacana Philippi (Rosaceae)

Abstract: Increasing elevation can restrict the expansion of tree species by negatively affecting growth. In this study, we estimated growth velocity and evaluated the effects of extreme elevation on radial growth of the Andean tree Polylepis tarapacana Philippi (Rosaceae). We also developed different models to predict the relationship between age (number of tree-rings) and allometric characters (total height and diameter). Samples of trees and shrubs were collected between 4,200 and 4,600 m asl and analyzed using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
0
10
0
10
Order By: Relevance
“…Polylepis species have slow growth rates. For example, Renison et al (2005) found that seedlings of Polylepis australis in Argentina at elevations of approximately 2000 m grow in height at a rate of 69 mm per year, Saravia and Vintimilla (2016) showed that Polylepis reticulata trees at ~ 3800 m in Ecuador grow in diameter at a rate of 0.78 and 1.17 mm per year for young and mature trees, respectively, and Domic & Capriles (2009) found that Polylepis tarapacana trees at elevations between 4200 and 4600 m in Bolivia grow in diameter at a rate of 4.6 mm per year. The study of the growth rates of different Polylepis species has been widely addressed by the scientific community (e.g., Colmenares 2002, Hoch & Körner 2005, Gareca et al 2010b, Duchicela 2011, Alvites et al 2019.…”
Section: Regeneration Capacitymentioning
confidence: 99%
“…Polylepis species have slow growth rates. For example, Renison et al (2005) found that seedlings of Polylepis australis in Argentina at elevations of approximately 2000 m grow in height at a rate of 69 mm per year, Saravia and Vintimilla (2016) showed that Polylepis reticulata trees at ~ 3800 m in Ecuador grow in diameter at a rate of 0.78 and 1.17 mm per year for young and mature trees, respectively, and Domic & Capriles (2009) found that Polylepis tarapacana trees at elevations between 4200 and 4600 m in Bolivia grow in diameter at a rate of 4.6 mm per year. The study of the growth rates of different Polylepis species has been widely addressed by the scientific community (e.g., Colmenares 2002, Hoch & Körner 2005, Gareca et al 2010b, Duchicela 2011, Alvites et al 2019.…”
Section: Regeneration Capacitymentioning
confidence: 99%
“…The differences between main-branch GUs at high and low positions regarding resource allocation to the stem and stem density can be related to their capacity to stand static and dynamic loads without buckling and, consequently, to grow closer to an upright orientation (Niklas 2007;Domic and Capriles 2009). This trait can allow main branches at higher positions to have an upward pointing to almost vertical orientation.…”
Section: Structural Axis Differentiation In Nothofagusmentioning
confidence: 99%
“…In mature, natural forests, the tree height-dbh (diameter at breast height) relationship usually shows a saturation effect because tree height is limited by ecological factors such as water and nutrient availability, or the lack of adequate thermal conditions ( Anfodillo et al, 2012 ; Lines et al, 2012 ; Marshall et al, 2012 ). Trees that have reached this potential maximum height cannot grow any taller but, as they increase in age, they continue to form new annual growth rings, thus increasing in diameter ( Domic and Capriles, 2009 ). By contrast, in disturbed forests where especially large trees are extracted, no such saturation is visible in the remaining tree cover.…”
Section: Introductionmentioning
confidence: 99%